The Museum Community and Community Museum Governance - Nelson, Robin (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2020)
Ontario has more than 500 museums, varying in type, size, and expressed need. They have different relationships to both government policy and the associations that represent them. Yet, research on museum governance often focuses on provincial or national organizations, neglecting community museums (i.e., smaller institutions with local or regional roots). Due to their limited resources, community museums rely on the work of spokespeople to advocate for their interests. Within Ontario museum governance, these spokespeople use the term “museum community” to indicate consensus on a course of action. According to a sociology of translation perspective, when a spokesperson speaks for others, they must first silence those in whose name they speak. As such, this paper considers how those governing the sector construct the “museum community” as actors in support of particular action. It asks who and what forms the museum community? Which voices are given a platform as museum advisors and which associations represent the so-called community? The paper concludes that municipal museums have historically had a privileged position within museum associations’ articulation of community, while provincial museum advisors have more successfully included the voices of small historical society museums. As the museum advisor’s resources have become more limited, the Ontario Museum Association (OMA) has taken a more active role in assembling those voices. However, the association has limited financial resources. As such, there continues to be a stratification of museums in museum governance.